Apetyt na Bragę. O intertekstualnym dialogu między Adolfem Pawińskim a Oswaldem Crawfurdem i o dziewiętnastowiecznym podróżowaniu - Magdalena Bąk (Postscriptum Polonistyczne)
The aim of the article is to compare the two different modes of regarding and describing Braga observed in Adolf Pawiński’s and Oswald Crawfurd’s works on Portugal. The Polish description is based on visual perception, while in a work by the English author other senses (hearing, taste and smell) are equally important. Therefore it might be assumed that Pawiński represents a more traditional style of travelling, while Crawfurd behaves in a way typical for modern tourists.